Canine demodicosis - KOUTINAS (Α.Φ. ΚΟΥΤΙΝΑΣ) A. F.; SARIDOMICHELAKIS (Μ.Ν. ΣΑΡΙΔΟΜΙΧΕΛΑΚΗΣ) M. N.; KOUTINAS (X.Κ. ΚΟΥΤΙΝΑΣ) C. K. (Journal of the Hellenic Veterinary Medical Society, 2018)
Canine demodicosis, which is caused by the follicular mite Demodex canis, is one of the most common skin diseases, especially in the young dog. Demodicosis can be localized or generalized; in the latter a parasite-specific cellular immunosuppression, which is genetically transmitted, is the cornerstone of its pathogenesis. Alopecia - hypotrichosis, erythema, hyperpigmentation, lichenification, papules, scales and crusts, first appear on the face and front limbs, to spread eventually to the other parts of the body. Superficial or deep staphylococcal pyoderma is a common complication, especially in the generalized form of the disease. Diagnosis will be confirmed by the presence of the mite in high numbers and at various developing stages in the skin scrapings. Treatment is not recommended for the localized form, which is almost always self-limiting. Various ectoparasiticides have been used in the generalized form of the disease, either for topical (amitraz) or systemic application (ivermectin, mylbemycin, moxidectin), with good results. Treatment is terminated when not a single parasite can be found in the skin scrapings on 2-3 consecutive monthly re-examinations. The animal is considered cured if there have not been any relapses one year since the end of the acaricidal treatment.